Decreased phagocytic function in neutrophils and monocytes from peripheral blood in periodontal disease - Carneiro, Valéria Martins Araújo (2012)
Phagocytosis by neutrophils and monocytes constitutes the main defense mechanism against bacterial challenges in periodontitis. Phagocytosis by neutrophils has already been evaluated, whereas phagocytic function of monocytes has hardly been addressed so far. Objectives: The aim of this study was to assess phagocytosis by neutrophils and monocytes in periodontitis. Material and Methods: The sample included 30 subjects with severe periodontitis and 27 control subjects without periodontal disease. The phagocytic index (PhI) was calculated as the mean number of adhered/ingested Saccharomyces cerevisiae per phagocytozing monocyte or neutrophil multiplied by the percentage of phagocytes involved in phagocytosis. Results: A significant reduction in phagocyte functions was observed in individuals with periodontitis. The median of PhI of neutrophils using nonsensitized S. cerevisiae was 3 for the control group, and 1.5 for the periodontitis group (p=0.01, Mann-Whitney test). The median of PhI of monocytes with non-sensitized S. cerevisiae was 26.13 for the control group, and 13.23 for the periodontitis group (p=0.03, Mann Whitney test). The median of PhI of monocytes assessed with sensitized S. cerevisiae was 97.92 for the control group and 60.1 for the periodontitis group (p=0.005, t-test). Conclusion: The data demonstrated a reduction in the function of phagocytes, suggesting a decrease in immune defenses in periodontitis.